Teacher professional experience and performance: impact of the work environment and general welfare in Malaysian secondary schools - Malakolunthu, S.; Idris, A.R.; Rengasamy, N.C. (Springer, 2010)
This study investigated the work environment and general welfare of the Malaysian secondary school teachers. Past studies have explicated that the experience of work environment and general welfare exerted a direct influence on the performance of the teachers, hence student outcome. In the factor analysis, the study identified six factors, namely collective purpose, respect and recognition, job design, health and learning, work load, and institutional support as the components of work environment affecting Malaysian teachers. When the factors were subjected to a survey inquiry, the results revealed that the Malaysian teachers were having an adverse professional experience with regard to the work environment and general welfare. Descriptive analysis and analyses of variance provided statistical support that there was consensus among the teachers about their professional experience. The findings may indicate the necessity for the policy community to give serious attention on improving the work conditions and general welfare of teachers for better performance and student outcomes at schools.